Reduced ejection fraction heart failure – new data from multicenter studies and national registries regarding general and elderly populations: hopes and disappointments - Crișan S (Dove Medical Press, 2018)
Simina Crişan,1,2 Lucian Petrescu,1,2 Mihai Andrei Lazăr,1,2 Cristina Văcărescu,1,2 Alina-Ramona Nicola,1 Dragoş Cozma,1,2 Cristian Mornoş,1,2 Constantin Tudor Luca1,2 1Cardiology Department, Victor Babes University of Medicine and Pharmacy, Timisoara, Romania; 2Institute of Cardiovascular Diseases, Timisoara, Romania Abstract: The evaluation of patients diagnosed with impaired systolic function heart failure represents a great challenge, in both the general and elderly population. We consider that elderly patients are the most severely affected by this disease that represents the final impact of cardiovascular disease continuum. Cardiovascular diseases are associated with serious morbidity and mortality, and considerable health care costs related to diagnosis and treatment. In this report we discuss some controversies regarding methods of heart failure evaluation as well as therapeutic steps and devices, including: reparatory therapeutic steps and initiation of therapy with loop diuretics, inconsistent dose titration for angiotensin-converting enzyme inhibitors/angiotensin receptor blocker and beta blockers, as well as novel therapies, such as angiotensin receptor neprilysin inhibitor and treatments that directly improve cardiomyocyte function. We conclude that, beyond technical progress, which is raising the cost of therapy for patients with heart failure, more careful monitoring of patient progress through clinical and paraclinical control visits, both at medical facilities and at home, would have greater impact and be more cost-effective. Physical therapy and promoting emotional and psychological wellbeing, to maintain a positive state of mind, contribute substantially to the quality of life and life expectancy, and are most important in elderly people who are most affected by dramatic reductions in wellbeing. Unfortunately, for many patients with severe impairment of left ventricular ejection fraction, these goals and therapeutic procedures are often lacking in current health care systems.Keywords: impaired left ventricular ejection fraction, heart failure, therapeutic controversies, elderly population